A Critical Review of Maslow's Theory of Spirituality. Issue 4 (2nd October 2022) - Papaleontiou–Louca, Eleonora; Esmailnia, Saeed; Thoma, Niki
ABSTRACT: Maslow's theory might be one of the most powerful perspectives on humans' growth. It suggests that people have a strong desire to realize their full potential, reach their self-actualization and find meaning in life. In spite of its attractive nature, the theory has also received much criticism. One of the main objections focuses on its emphasis on "self", which might be interpreted as an individualistic perspective of life. Maslow's later addition of the "Transcendence" level seems more compatible with the notion of "spirituality" since people seem, now, to be able to overcome "self" and commit themselves to a higher goal.